EXAMINING THE RELATIONSHIP OF FUNDS COLLECTED AND FUNDS ALLOCATED WITH RETURN ON ASSETS IN TURKISH PARTICIPATION BANKING SECTOR BEFORE(2018-2019) AND AFTER COVID-19(2020-2021) (Third Sector Social Economic Review, 2024)
The crisis caused by the COVID-19 pandemic has affected all institutions in the financial system in various ways, and since it is an important part of the financial sector, participation banks have also been affected by this process. In this study, it is aimed to examine the relationship between the funds collected and used by the five participation banks operating in Turkey before COVID-19 (2018-2019) and after the COVID-19 pandemic (2020-2021) and their return on assets. In this context, data on financial ratios and profitability ratios related to fund collection and fund disbursement have been compiled for the quarterly periods between 2018-2021; The data were analyzed in the SPSS 23 program. Before the analysis, normality test was performed on the skewness and kurtosis coefficients of the data, and it was determined that the data were normally distributed. The VIF values of the data were examined and it was determined that there was no multicollinearity between the variables. Anova tests and regression analyses were performed to compare the data for the period before and after the COVID-19 pandemic. According to the results of the study, it has been determined that the variables “TP Funds Allocated / Total Funds Allocated (F1)”, “Total Funds Allocated / Total Assets (F2)” and “Total Funds Collected / Total Assets (F3)” explain the return on assets of participation banks in Turkey. It has been found that the data on all variables related to the period before and after the COVID-19 pandemic differ statistically significantly. During the COVID-19 pandemic, the effect of the "" Total Funds Allocated / Total Assets"" ratio on the return on assets of participation banks reversed and turned negative.
Keywords: Participation bank; funds collected; funds allocated; return on assets; Islamic finance.